2016
DOI: 10.1111/ases.12218
|View full text |Cite
|
Sign up to set email alerts
|

Totally laparoscopic gastrectomy for early gastric cancer accompanied by huge hiatal hernia: A case report

Abstract: We herein present a case in which we used a totally laparoscopic approach for early gastric cancer accompanied by a huge hiatal hernia. An 80-year-old Japanese woman was referred with a chief complaint of dysphagia. A clinical diagnosis of early gastric cancer, T1b (SM) N0M0, stage IA, accompanied by hiatal hernia, was made. Distal gastrectomy with D1 plus lymphadenectomy was carried out. After the gastrectomy, the hernial sac was excised and the hernial orifice was closed. Reconstruction using the Roux-en-Y m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“… 3 Hagiwara et al reported on five patients who underwent laparoscopic gastrectomy for gastric cancer accompanied by huge hiatal hernia. 2 In this case, preoperative endoscopic examination revealed an EGC for an ESD adaptation. Endoscopic treatment or surgery must be selected according to the gastric cancer stage; hence, it is necessary to check for malignant diseases such as esophageal and gastric cancer before surgery for an esophageal hiatal hernia.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“… 3 Hagiwara et al reported on five patients who underwent laparoscopic gastrectomy for gastric cancer accompanied by huge hiatal hernia. 2 In this case, preoperative endoscopic examination revealed an EGC for an ESD adaptation. Endoscopic treatment or surgery must be selected according to the gastric cancer stage; hence, it is necessary to check for malignant diseases such as esophageal and gastric cancer before surgery for an esophageal hiatal hernia.…”
Section: Discussionmentioning
confidence: 79%
“…Mimatsu et al reported the clinicopathological characteristics, treatment, and outcomes of 14 patients with gastric cancer from the upside‐down stomach through a paraesophageal hernia 3 . Hagiwara et al reported on five patients who underwent laparoscopic gastrectomy for gastric cancer accompanied by huge hiatal hernia 2 . In this case, preoperative endoscopic examination revealed an EGC for an ESD adaptation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…12 Diaphragmatic hernia (DH) is an iatrogenic condition in which the abdominal contents herniate into the thoracic space through the hiatus. 13 Although DH is a rare complication of IH after TLTG, it merits concern because this hernia can dramatically present as an acute bowel obstruction with bowel necrosis. Especially, delayed surgical intervention may result in bowel perforation with high morbidity and mortality.…”
mentioning
confidence: 99%